Association of dietary index for gut microbiota with frailty in middle-aged and older Americans: a cross-sectional study and mediation analysis - Xiaodan Li; Xiaodan Li; Ying Liu; Chuyi Shen; Changzhuan Shao; Hongke Jiang (Frontiers in Nutrition, 2025)
BackgroundWhile frailty poses significant challenges in aging populations, evidence regarding gut microbiome-targeted nutritional strategies remains limited. The novel Dietary Index for Gut Microbiota (DI-GM), quantifying microbial-pertinent dietary patterns, provides a framework for personalized frailty mitigation.MethodsThis cross-sectional study analyzed 12,914 middle-aged and older Americans (≥45 years) from National Health and Nutrition Examination Survey 2005–2018. Frailty status was assessed using a validated 49-item index (non-frail ≤0.21; frail >0.21). The DI-GM (range 0–10) was derived from 14 microbiota-linked dietary components through two 24-h recall interviews. Multivariable logistic regression with sensitivity analyses, restricted cubic splines (RCS), stratified analyses, and mediation effect were implemented to systematically evaluate DI-GM-frailty associations.ResultsAdjusted analyses revealed a dose-dependent inverse association between DI-GM and frailty (OR = 0.86, 95%CI: 0.84–0.88 per unit increase). RCS identified a nonlinear inflection at DI-GM = 4.082 (p for nonlinearity = 0.031), beyond which each unit elevation corresponded to 12.6% reduced frailty probability (OR = 0.874, 95%CI: 0.806–0.947). Stratified analyses demonstrated enhanced protective effects in women (OR = 0.84 vs. male 0.90; p for interaction = 0.011) and college-educated individuals (OR = 0.85 vs. 0.93; p for interaction = 0.031). Mediation analysis indicated BMI mediated 38.28% (95%CI: 26.62–62.6, p < 0.001) of the DI-GM effect on frailty progression.ConclusionHigher DI-GM scores associate with lower frailty prevalence, particularly among women and highly-educated populations, partially mediated through BMI modulation. These findings establish DI-GM as a microbiota-targeted nutritional guideline for age-related frailty interventions, bridging dietary patterns with microbial homeostasis in geriatric care.